Causal Relationship Model of Hospital Environmental Management - Jongwutiwes, Nipaporn; Thiengkamol, Nongnapas; Thiengkamol, Tanarat (Richtmann Publishing, 2012)
The populations were 270 workers of Roi-ed Thonburi Hospital in Northeastern region of Thailand. The populations of270 workers were used as sample group. The questionnaire was used as instrument for data collection. LISREL was used formodel verification. Considering on structural model confirmatory factors of Environmental Education (EE) and HospitalEnvironmental Management (EM) were able to explain the variation of endogenous factors of Inspiration of PublicConsciousness (PM) to caused Environmental Conservation Behaviors (CB) with 72.00 percents. As a result, the equation 1 canbe written as following.CB = 0.51*PM - 0.13*EE + 0.34*EM ………………………………(1)R2 = 0.72Equation (1) factors that had the most effect to Environmental Conservation Behaviors (CB) was Inspiration of PublicConsciousness (PM) and subsequences were Hospital Environmental Management (EM) and Environmental Education (EE)with negative direction, these were able to explained the variation of Environmental Conservation Behaviors (CB) with 72.00percents.Moreover, confirmatory factors of Environmental Education (EE) and Hospital Environmental Management (EM) wereable to explain the variation of confirmatory factors of Inspiration of Public Consciousness (PM) with 63.00 percents. Therefore,the equation can be written as following equation 2.PM = 0.17*EE + 0.44*EM …………………………..…………….(2)R2 = 0.63Equation (2) factors that had the most effect to was Inspiration of Public Consciousness (PM) and subsequences were HospitalEnvironmental Management (EM) and Environmental Education (EE), these were able to explained the variation of Inspiration ofPublic Consciousness (PM) with 63.00 percents